My Conceptions shape my Practices’, Palestinian Mathematics Teachers’ Conceptions and Practices in Fostering Creativity - Kowkas, Sultan Amin (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2024)
As many abstract terms, creativity is understood differently by people, each according to his/her cognitive background. In addition, creativity is such a sophisticated concept, that its interpretation has constantly evolved over the progression of epochs and within the development of cultures and civilizations. Its schema has transformed over a wide spectrum of descriptions, from the notion of Divine inspiration adopted by early philosophers to the modern outlooks of originality and problem-solving skills. On the other hand, people behave according to their inner beliefs and based on their interacted ideologies. Wherefore, the current study explores 8th and 9th grade, Palestinian Mathematics teachers’ conception of Mathematical Creativity (MC), as well as their teaching practices in fostering MC among students.‎ The study used semi-structured interviews with twenty in-service Mathematics teachers, exploring their conceptions, teaching strategies and interpreting their features in the context of fostering MC in class. The findings revealed that many teachers have good, but not full conception of MC whereas few had misconceptions. Those of good conceptions also integrate teaching practices that aim to foster MC, while those with misconceptions do not. In addition, teachers who believe in their students’ potentials adopt integrating MC-fostering’ practices while those with little belief do not. Moreover, teachers who involve in teaching practices that foster MC were noticed to have positive attitude toward Professional Development. Common challenges and obstacle hindering MC were mentioned by teacher; including official textbook issues, insufficient number of periods and large class sizes.